3D Printing of a Biocompatible Double Network Elastomer with Digital Control of Mechanical Properties. (19th February 2020) - Wang, Pengrui; Berry, David B.; Song, Zhaoqiang; Kiratitanaporn, Wisarut; Schimelman, Jacob; Moran, Amy; He, Frank; Xi, Brian; Cai, Shengqiang; Chen, Shaochen
Abstract: The majority of 3D‐printed biodegradable biomaterials are brittle, limiting their application to compliant tissues. Poly(glycerol sebacate) acrylate (PGSA) is a synthetic biocompatible elastomer and compatible with light‐based 3D printing. In this article, digital‐light‐processing (DLP)‐based 3D printing is employed to create a complex PGSA network structure. Nature‐inspired double network (DN) structures consisting of interconnected segments with different mechanical properties are printed from the same material in a single shot. Such capability has not been demonstrated by any other fabrication techniques so far. The biocompatibility of PGSA is confirmed via cell‐viability analysis. Furthermore, a finite‐element analysis (FEA) model is used to predict the failure of the DN structure under uniaxial tension. FEA confirms that the DN structure absorbs 100% more energy before rupture by using the soft segments as sacrificial elements while the hard segments retain structural integrity. Using the FEA‐informed design, a new DN structure is printed and tensile test results agree with the simulation. This article demonstrates how geometrically‐optimized material design can be easily and rapidly constructed by DLP‐based 3D printing, where well‐defined patterns of different stiffnesses can be simultaneously formed using the same elastic biomaterial, and overall mechanical properties can be specifically optimized for different biomedical applications. Abstract : Poly(glycerol sebacate) acrylate (PGSA) is synthesized. Projection light 3D printing enables rapid fabrication of double network (DN) structures with different mechanical properties at specific locations with a single shot and the same PGSA material. Finite‐element analysis guides the DN design. Experimental testing demonstrates that the DN structure achieves a 100% increase in toughness and is highly biocompatible.